Novel Alleles for Combined Drought and Heat Stress Tolerance in Wheat - Schmidt, Jessica; Tricker, Penny J.; Eckermann, Paul; Kalambettu, Priyanka; Garcia, Melissa; Fleury, Delphine (Frontiers in Plant Science, 2020)
Drought and heatwaves commonly co-occur in many wheat-growing regions causing significant crop losses. The identification of stress associated quantitative trait loci, particularly those for yield, is problematic due to their association with plant phenology and the high genetic × environment interaction. Here we studied a panel of 315 diverse, spring type accessions of bread wheat (Triticum aestivum) in pots in a semi-controlled environment under combined drought and heat stress over two years. Importantly, we treated individual plants according to their flowering time. We found 134 out of the 145 identified loci for grain weight that were not associated with either plant phenology or plant height. The majority of loci uncovered here were novel, with favorable alleles widespread in Asian and African landraces providing opportunities for their incorporation into modern varieties through breeding. Using residual heterozygosity in lines from a nested association mapping population, we were able to rapidly develop near-isogenic lines for important target loci. One target locus on chromosome 6A contributed to higher grain weight, harvest index, thousand kernel weight and grain number under drought and heat stress in field conditions consistent with allelic effects demonstrated in the genome-wide association study.